Functional characterization and discovery of modulators of SbMATE, the agronomically important aluminium tolerance transporter from Sorghum bicolor. Issue 1 (December 2017) - Doshi, Rupak; McGrath, Aaron; Piñeros, Miguel; Szewczyk, Paul; Garza, Denisse; Kochian, Leon; Chang, Geoffrey
Abstract About 50% of the world's arable land is strongly acidic (pH ≤ 5). The low pH solubilizes root-toxic ionic aluminium (Al3+ ) species from clay minerals, driving the evolution of counteractive adaptations in cultivated crops. The food cropSorghum bicolor upregulates the membrane-embedded transporter protein SbMATE in its roots. SbMATE mediates efflux of the anionic form of the organic acid, citrate, into the soil rhizosphere, chelating Al3+ ions and thereby imparting Al-resistance based on excluding Al+3 from the growing root tip. Here, we use electrophysiological, radiolabeled, and fluorescence-based transport assays in two heterologous expression systems to establish a broad substrate recognition profile of SbMATE, showing the proton and/or sodium-driven transport of14C -citrate anion, as well as the organic monovalent cation, ethidium, but not its divalent analog, propidium. We further complement our transport assays by measuring substrate binding to detergent-purified SbMATE protein. Finally, we use the purified membrane protein as an antigen to discover native conformation-binding and transport function-altering nanobodies using an animal-free, mRNA/cDNA display technology. Our results demonstrate the utility of usingPichia pastoris as an efficient eukaryotic host to express large quantities of functional plant transporter proteins. The nanobody discovery approach is applicable to other non-immunogenic plant proteins.